Determinants Influencing Tribal Youth Engagement in Agricultural Livelihood Pursuits in Dindori District, Madhya Pradesh, India - Geeta Singh; M. K. Dubey; S. R. K. Singh; R. B. Singh (Contemporary Research in Business, Management and Economics Vol. 9, 2024)
The present study primarily focuses on determinants Influencing Tribal Youth Engagement in Agricultural Livelihood Pursuits in Dindori District, Madhya Pradesh, India. Rural areas are the economic backbone of most developing countries and contribute to their overall economic growth through the creation of jobs and the supply of food and raw materials to other growing sectors of the economy. While the modes of living of various populations in tribal areas vary, all groups of people in these places rely either entirely or partially—directly or indirectly—on agriculture for their subsistence. Some social groupings are still very far apart from pastoralism and agriculture, making it impossible for them to reach the stage of agriculture. The Baigas, a people group in Central India, are now compelled to engage in established agriculture. Before they practiced shifting cultivation, they had various modes of livelihood. They still enjoy their traditional mode of livelihood, i.e. hunting and food gathering in the deep forest. They are also fond of fishing. Many tribal youths are faced with difficulty of maintaining livelihoods and consequently, poverty remains exist among them. The importance of income-generating activities to tribal livelihood cannot be over-emphasized. This paper examines the factors influencing the involvement of tribal youth in agricultural income generating livelihood activities in Dindori district of Madhya Pradesh, India. Purposive multistage random sampling was used to collect data from 250 respondents, the majority of respondents had medium mass media exposure with medium urban contact for income-generating activities. There was a significant relationship between involvement in agricultural income-generating activities and the socio-personal-economic, psychological and communicational attributes of the respondents. The study concludes that the main factors affecting livelihood patterns among tribal youth in the Dindori district of Madhya Pradesh are; marital status, family type, social participation, land holding, family income, rural life preference, urban contact, mass media exposure and reasons for educational and vocational training. It is advised that the government and non-governmental organizations (NGOs) consider all agricultural income-generating activities that tribal youths participate in, as well as the factors mentioned above that impact their involvement when designing and organizing programs targeted at improving the livelihoods of these youths.